Hubungan Antara Pola Asuh dengan Perilaku Prososial pada Anak Usia Dini - Aulia, Putri; Siregar, Jihan Fadiyah Fitri (Lembaga Yasin AlSys, 2022)
Parenting is the way parents nurture, guide, train and direct their children. Caring for children is also the mindset and behavior of parents towards their children. Prosocial behavior is behavior that inevitably impacts others, fostering self-serving behavior without expecting anything for yourself. Prosocial behavior is behavior that is expected to provide physical or mental blessings to others. the prosocial behavior instilled in people from the formative years leads to charm and sophisticated social intelligence. Of course, when humans get used to prosocial behavior, children with excessive curiosity become very important, and this curiosity can be proven in a positive way.